Determination Stability of 99mTc-Etambutol Radiopharmaceuticals for Tuberculosis Detected - Anna Roseliana; Witarti Witarti; Enny Lestari; Maula Eka Sriyani; Widyastuti Widjaksana (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
99mTc-ethambutol radiopharmaceutical is a diagnostic kit based on the anti-tuberculosis drug, ethambutol, labeled with radioactive tracer 99mTc. This radiopharmaceutical is a result of research development in Centre for Radioisotope and Radiopharmaceutical Technology, BATAN. 99mTc-ethambutol radiopharmaceutical in the hospital used as a diagnostic agent for tuberculosis detected, particularly tuberculosis in extra pulmonary organs that is not easily detected by existing conventional methods. The aim of study to find out how stable ethambutol kit when stored at certain temperature and how stable ethambutol stability after labelled with 99mTc. These stability data are required by hospitals which used 99mTc-ethambutol . The stability test performed by measuring the radiochemical purity of ethambutol kits which were stored at certain time period and labelled with 99mTc using thin layer chromatography (TLC) method. Radiochemical purity tests were also performed on 99mTc-ethambutol at certain time period after its labeling process. Based on experiment results, it was obtained that ethambutol kit was still stable for up to 9 months when stored at refrigerator temperature 8 oC with percentage of radiochemical purity average > 85% and up to 11 months when stored in deep freezer temperature -80 oC with percentage of radiochemical purity average 90%. While 99mTc-ethambutol was still stable for up to 4 hours after labeling with percentage of radiochemical purity more than > 85%.